2022
DOI: 10.21542/gcsp.2022.8
|View full text |Cite
|
Sign up to set email alerts
|

Inari large-bore mechanical thrombectomy in intermediate-high risk submassive PE patients: Case series and literature review

Abstract: Pulmonary embolism (PE) is one of the most common causes of cardiovascular (CV) mortality worldwide. Owing to the associated morbidity and mortality with other treatment modalities, including systemic thrombolysis, a discernible change in the era of acute pulmonary embolism management has been reported. Catheter-directed thrombectomy using the FlowTriever system (Inari Medical; Irvine, CA, USA) was shown to reduce endpoints of interest in patients with acute intermediate-high risk PE and was associated with ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Mathbout et al [ 12 ] presented a case series and literature review of three intermediate-high risk submassive PE patients treated with the FlowTriever ® system. The authors reported a significant reduction in pulmonary artery systolic pressure and improvement in right ventricular function in all patients that can be related to our experiences with the presented case.…”
Section: Discussionmentioning
confidence: 99%
“…Mathbout et al [ 12 ] presented a case series and literature review of three intermediate-high risk submassive PE patients treated with the FlowTriever ® system. The authors reported a significant reduction in pulmonary artery systolic pressure and improvement in right ventricular function in all patients that can be related to our experiences with the presented case.…”
Section: Discussionmentioning
confidence: 99%